Aplikasi Game Edukasi pada Anak Usia 5 Sampai 10 Tahun dengan Metode Image Manipulation - Irohito Nozomi (INTECOMS: Journal of Information Technology and Computer Science, 2018)
At present we have found a lack of learning media applications that can attract the attention of children in the learning process, especially children aged 5 to 10 years. Educational games need to be developed, because learning games have advantages over conventional learning. The main advantages of learning games are in the appearance of the real problem. Learning games are designed to be examples of existing problems so that values ​​or knowledge can be used to solve the problem. This learning simulation game aims for entertainment and can be used as one of the media that overcomes boredom and boredom in the learning process and educates students. Based on the pattern that this learning game has, users are required to learn to complete the existing learning. Promotes learning games that are superior in some respects when compared to old learning methods. One obvious advantage is animation that can increase children's memory, so children can store learning material for a long time, when compared to conventional learning. Keywords : Education Game, Children, Image Manipulation